Tomato From Cultivation to Processing Technology - Viškelis, Pranas; Urbonavičienė, Dalia; Viškelis, Jonas (IntechOpen, 2022)
The tomato is a valuable vegetable, popular all over the world. This book covers interesting research topics including tomato plant nutrition, production and chemical composition, tomato plant protection, and sustainable tomato processing technologies. This book will be of value to researchers, academics, and students in the field of agronomy, food, pharmacy, and other sectors.